2019
DOI: 10.15803/ijnc.9.2_370
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of high speed hash function Keccak on GPU

Abstract: Nowadays, a hash function is used for password management. The hash function is desired to possess the following three characteristics: Pre-Image Resistance, Second Pre-Image Resistance, and Collision Resistance. They are set on the assumption that it is computationally difficult to find the original message from a given hash value. However, the security level of the password management will be further reduced by implementing a high speed hash function on GPU. In this paper, the implementation of high speed ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this section, we present the SHA-3 performance results using CUDA Stream. A previous work by Dat et al showed a throughput of up to 64.58 Gb/s using three CUDA streams [24]. We present the results of SHA-3 implementation in GTX 1070 and RTX 2080Ti architecture environments.…”
Section: B Analysis With the Application Of Cuda Streammentioning
confidence: 84%
See 2 more Smart Citations
“…In this section, we present the SHA-3 performance results using CUDA Stream. A previous work by Dat et al showed a throughput of up to 64.58 Gb/s using three CUDA streams [24]. We present the results of SHA-3 implementation in GTX 1070 and RTX 2080Ti architecture environments.…”
Section: B Analysis With the Application Of Cuda Streammentioning
confidence: 84%
“…In this paper, we proposed an effective parallel message copy of input data and kernel execution methods by applying CUDA stream and we provided the result of SHA-3 implementation using CUDA stream. Also, in SHA-3 implementation, performance using CUDA stream, we present the result of comparing Dat et al's proposal and our implementation [22], [24]. Our optimized implementation of SHA-3 using 3 CUDA streams provides the maximum throughput of 95.67Gb/s in a GTX 1070 environment.…”
Section: Sha-3 Internal Statementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, research on ECC using GPU architecture is continuously being conducted [31][32][33]. Research on block cipher algorithms and hash functions in GPU architectures has also been published [34][35][36][37][38][39][40][41]. However, there are no studies of hash functions using AVX-512 and LSH optimization research implementation using GPUs.…”
Section: Introductionmentioning
confidence: 99%
“…During and after the NIST's competition several implementations of SHA-3 are presented [8]- [17], [18]. In spite of the availability of software implementations of security algorithms using high powerful central processing unit (CPUs) [19], hardware implementations of these algorithms using high developed platforms such as fieldprogrammable gate arrays (FPGAs) and application specific integrated circuit (ASICs) remains greatly demanded.…”
Section: Introductionmentioning
confidence: 99%